Unmasking the Effect of News Media on Islamic Stock Market: Are ASEAN-3 Countries Vulnerable to COVID-19 News? - Syarifa Rahmi; Nur Fatwa; Agung Maulana (Shirkah: Journal of Economics and Business, 2023)
This study provides a novel viewpoint by clarifying the effect of the COVID-19 news on the fluctuations of the Islamic capital market in the ASEAN Region. It aims to explore the effect of news related to the COVID-19 pandemic on the movement of the Islamic stock index in ASEAN-3 countries (Indonesia, Malaysia, Thailand). This research examined five news-related indices: panic emotion index, media hype index, sentiment index, fake news index, and contagion index. The research employed long-term daily secondary data covering one year during the COVID-19 pandemic to test the hypothesis. A total of 1086 data were analyzed using the panel regression method through EViews 9. The findings indicated that news media and the resulting sentiment have the potential to negatively affect the Islamic stock index movement through the panic and media hype index. The excitement and panic caused by the online news media negatively affected the movement of Islamic stock prices in the three ASEAN Islamic stock indexes, whereas fake news and contagion index were found to have no significant effect on the stock index movement.